Assessing state ESSA plans: Innovation or retreat?. (October 2019) - McGuinn, Patrick
Three years after the passage of the Every Student Succeeds Act (ESSA), Patrick McGuinn reviews how the U.S. Department of Education has managed the approval process for state accountability plans, how state plans are shaping up as a result of their newfound flexibility, and what implementation challenges have emerged. States have required multiple iterations to submit plans that the Department of Education would approve, and state plans have met with criticism from multiple quarters and across the political spectrum. Some states have adopted new practices related to testing and which measures to use to assess schools. However, it is not yet clear what the long-term effects that the giving of greater flexibility to the states will have .